TRANSAKSI E-COMMERCE SEBAGAI POTENSI PENERIMAAN PAJAK DI INDONESIA - MAHARANI UTOMO, EVIERA Maharani (Jurnal Akuntansi AKUNESA, 2013)
Indonesia's tax revenue in 2012 is still under the budget. The increase of the number of taxpayers each year is still not able to cover the deficit. E-commerce, which the amounts are increasing each year, can be one right solution to resolve the issue.One of the factors that could affect e-commerce is Indonesia internet user which also increases every year. Unfortunately, Directorate General of Taxes still has not decided the perfect regulations for e-commerce transaction in Indonesia. Indonesia needs to define which transactions should be taxed.  This research aims to know the potential tax revenue from e-commerce transaction in Indonesia, especially income taxes and Value Added Taxes (VAT). Key words: tax, e-commerce, income taxes, Value Added Taxes (VAT)